2018
DOI: 10.1590/1806-9061-2017-0614
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Threonine on Performance Parameters, Carcass Traits, Visceral Organ Indices and Serum Biochemical Parameters of Linwu Ducks, Aged 4 to 8 Weeks

Abstract: This study was conducted to establish dietary threonine (Thr) levels for Linwu ducks, aged 4 to 8 wk. Experimental diets formulated to contain 0.56, 0.61, 0.66, 0.71, 0.76, and 0.81% Thr fed to Linwu ducks. A total of 360 healthy Linwu female ducks with similar body weight (1183.89±3.83 g) were randomly divided into six groups, with five replicates in each group, and 12 ducks in each replicate. Samples were collected at 8 wk for the determination of growth performance, carcass traits, visceral organ indices, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This was in agreement with Liu et al [24], who reported Yangzhou geese in NRS exhibited higher subcutaneous fat thickness and higher AFY than in FRS. The visceral organ development is closely associated with duck growth, development, and health [30]. Results showed GW and GI were generally lower in NRS at different ages, indicated that FRS ducks had better gizzard development than NRS ducks.…”
Section: Discussionmentioning
confidence: 95%
“…This was in agreement with Liu et al [24], who reported Yangzhou geese in NRS exhibited higher subcutaneous fat thickness and higher AFY than in FRS. The visceral organ development is closely associated with duck growth, development, and health [30]. Results showed GW and GI were generally lower in NRS at different ages, indicated that FRS ducks had better gizzard development than NRS ducks.…”
Section: Discussionmentioning
confidence: 95%
“…The FCR value, according to Panase and Mengumphan [21] A total of three chickens aged 21 days from each replication were euthanized and the viscera of the heart, liver, spleen, pectoralis muscle tissue, gastrocnemius, and small intestine were taken. Measuring the index of viscera organs can be an indicator to know the balance of growth performance [22]. The left muscle tissue was collected to measure the muscle area, while the right muscle tissue was made for histological preparations.…”
Section: Measuring Feed Conversion Ratio (Fcr)mentioning
confidence: 99%